2019
DOI: 10.1029/2019ja027382
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Jupiter's Dawn Magnetosheath Using Juno

Abstract: The Juno spacecraft crossed Jupiter's bow shock and into the magnetosheath on 24 June 2016.It then went into 53-day polar orbits with its apojoves at 113 Jovian radii on Jupiter's dawn side. These orbits have given us a unique opportunity to survey Jupiter's dawn magnetosheath. Using data from the Jovian Auroral Distributions Experiment, the Magnetic Field Investigation, and the Waves Investigation, we have identified 91 magnetosheath crossings for a total of 48.2 days of data. We present the statistical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 90 publications
(164 reference statements)
1
52
0
Order By: Relevance
“…Between 60 and 110 R J , an indication of magnetosheath encounters is shown with enhancements in counts. Variability of magnetosheath distance is due to a change in the upstream solar wind conditions (e.g., McComas et al, ; Ranquist et al, ; Wilson et al, ). The equatorially confined plasma observed between ∼10 and ∼50 R J represents plasma sheet ions.…”
Section: Instrumentation and Datamentioning
confidence: 99%
“…Between 60 and 110 R J , an indication of magnetosheath encounters is shown with enhancements in counts. Variability of magnetosheath distance is due to a change in the upstream solar wind conditions (e.g., McComas et al, ; Ranquist et al, ; Wilson et al, ). The equatorially confined plasma observed between ∼10 and ∼50 R J represents plasma sheet ions.…”
Section: Instrumentation and Datamentioning
confidence: 99%
“…The second assumption is a looser variation on the assumption that the magnetosheath magnetic field lies tangentially to the magnetopause surface. Unfortunately, the stricter assumption breaks down since Ranquist et al (2019) showed that the magnetosheath magnetic field direction is frequently 25° farther away from aligned with the X axis than the velocity vectors. This implies that the plasma flow is more likely to lie tangentially to the magnetopause surface than the magnetic field.…”
Section: Methodsmentioning
confidence: 99%
“…These results can be used to better understand the preferential rotation of the magnetic field in the magnetosheath to align with Jupiter's spin axis (Erkaev et al, 1996;Farrugia et al, 1998;Ranquist et al, 2019), which in turn changes the dynamics of magnetic reconnection and the Kelvin-Helmholtz instability at the Figure 3. The equatorial portion of the Joy et al (2002) model combined with a polar flattening of 1.29 ± 0.29 for the (a) JSN X-Z cross section and (b) JSN Y-Z cross section at the terminator.…”
Section: Figure 3 Combines Thementioning
confidence: 99%
See 2 more Smart Citations